RANCANG BANGUN APLIKASI MOBILE LEARNING BELAJAR HURUF HIJAIYAH BERBASIS ANDROID - Jodi Hendrawan (Jurnal Abdi Ilmu, 2021)
Mobile learning is a learning process that utilizes technological developments through electronic devices such as smartphones or mobile phones. Currently learning hijaiyah is still mostly done by meeting directly with the teaching staff, through Iqra or other print media. With this it is considered less effective and inefficient and causes boredom for children. Because of this, we need an efficient, effective and interactive hijaiyah letter learning media that can increase children's interest in learning anywhere and anytime. The application will be designed with a system design tool, namely UML (Unified Modelling language) which is easy to describe so that it can assist in system design. The application will be implemented on android-based mobile devices.